The Effect of Accounting Information Systems, E-commerce, and Social Media with Business Strategy as a Moderating Variable on MSME Performance in Karawang Regency - Rafidah, Aufa; Permatasari, Ditya (Jurnal Akuntansi, Manajemen dan Ekonomi, 2024)
This study aims to determine the effect of accounting information systems, e-commerce, and social media on MSME performance and the role of business strategy in moderating the effect of accounting information systems, e-commerce, and social media on MSME performance in Karawang Regency. This study uses a quantitative approach, the population in this study were all MSMEs in Karawang district in 2021, the sample in this study were 100 respondents with the sampling technique using purposive sampling technique. The data used in this study are primary data obtained from distributing questionnaires to respondents directly. The data analysis technique used is multiple linear regression analysis using SPSS 26 software. The results of the analysis in this study indicate that accounting information systems and social media have a positive effect on the performance of MSMEs in Karawang Regency, e-commerce has no effect on the performance of MSMEs in Karawang Regency, business strategy cannot moderate the effect of accounting information systems, e-commerce, and social media on the performance of MSMEs in Karawang Regency. This study provides implications for MSMEs in Karawang Regency by applying technology such as accounting information systems, e-commerce, and social media can improve the performance of MSMEs.